2020
DOI: 10.3390/bs10020058
|View full text |Cite
|
Sign up to set email alerts
|

Interconnection between Driving Style, Traffic Locus of Control, and Impulsivity in Bulgarian Drivers

Abstract: The need for research in the field of transport psychology in Bulgaria has become more tangible in recent years, due to both the increased public intolerance to aggressive driving and the very high number of injuries and fatalities in road accidents in the country. The main objective of this study is to investigate the interconnection between Driving style, Traffic locus of control, and the Impulsivity in Bulgarian drivers. A research is conducted in order to examine the relations between the constructs in Bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
1
10
0
1
Order By: Relevance
“…Multi-group SEM analysis using the locus of control (LC) showed that both internality and externality were behavior-influencing factors [31], in accordance with Rotter [12]. Factor analysis also supported behavioral-leading attitudes, in agreement with Champahom et al [23], Lajunen and Räsänen [24], and Totkova [25]. The indicator other people [35], family or friend refer to Externality (EX) significantly following Transport Scotland [36] and Gicquel et al [37], while accident news, public campaign on safe riding have also been involved in reducing unsafe driving behavior [38], as well as policy and law enforcement [39].…”
Section: Discussion Of Lcsupporting
confidence: 63%
See 1 more Smart Citation
“…Multi-group SEM analysis using the locus of control (LC) showed that both internality and externality were behavior-influencing factors [31], in accordance with Rotter [12]. Factor analysis also supported behavioral-leading attitudes, in agreement with Champahom et al [23], Lajunen and Räsänen [24], and Totkova [25]. The indicator other people [35], family or friend refer to Externality (EX) significantly following Transport Scotland [36] and Gicquel et al [37], while accident news, public campaign on safe riding have also been involved in reducing unsafe driving behavior [38], as well as policy and law enforcement [39].…”
Section: Discussion Of Lcsupporting
confidence: 63%
“…Lajunen and Räsänen [24] used the LC to examine bicycle using behavior. Totkova [25] analyzed individual riding patterns activated by anger, anxiety, as well as dissociative, distress-reduction, high velocity, irrational, patient, careful, and risky styles.…”
Section: Locus Of Control (Lc)mentioning
confidence: 99%
“…Dampak rendahnya kendali kognitif sendiri adalah timbulnya perilaku maladaptif dan dapat menurunkan kemampuan individu untuk bereaksi terhadap lingkungan secara efisien, adaptif, dan dapat diterima (Bantjes dkk, 2019). Perilaku aggressive driving sendiri merupakan manifestasi gaya berkendara yang maladaptif (Totkova, 2020). Selain itu, penelitian Zajenkowki dan Zajenkowska (2015) secara umum menemukan hubungan negatif antara kendali kognitif dengan perilaku agresi.…”
Section: Hasil Dan Pembahasanunclassified
“…This study aims to address this research gap and explore the influences of age and driving experience, and their interactions on aggressive driving behavior. A cross-sectional survey collected the data and other confounding factors that could impact aggressive driving behavior in actual traffic environments were controlled for in the analyses including personality 28 , 45 , 46 and alcohol use disorders, 47 , 48 social supports, 49 , 50 negative emotion (depressive and anxiety symptoms), 11 , 51 , 52 and poor sleep quality. 53 , 54 The findings of this study will contribute to understanding aggressive driving behavior and may assist in the early identification of high-risk or accident-prone drivers, thus enabling the early prevention of traffic accidents.…”
Section: Introductionmentioning
confidence: 99%